Efek Pemberian Minyak Zaitun (Olive oil) Terhadap Perubahan Profil Lipid Pada Tikus putih (Rattus novergicus) - Syamsu, Rachmat Faisal (Fakultas Farmasi UMI, 2017)
This research aims to know the effects of olive oil to changes profil lipid (total cholesterol, LDL, HDL, and triglycerides) in the blood of the Rattus novergicus who were given a high cholesterol diet. This research is experimental research methods laboratory with pre and post test control . Homogeneous data and normal data next performed a test of paired t-Test and LSD test. All test data using the 95% significance level (p = 0.05). Conclusion of this research is the olive oil was able to lower the lipid profile, cholesterol 22,61%, LDL 38,48%, triglycerides 17.61% and increase the HDL 25.32% in the blood of rats high cholesterol diet